The Effect Of Hots-based Qira'ah Learning Evaluation with Quizizz Application on Students’ Learning Outcomes (Experimental Research at Markaz Arabiyah Course Institutions) - M Syahrul Anwar; Danial Hilmi; Rachmawaty Rachmawaty; Abdul Rasyid Hidayat (INAIFAS PRESS, 2023)
The world that continues to change requires education to adapt in using digital tools. This era-relevant of evaluation is based on HOTS with Quizizz. The use of Quizizz which educational is expected students to be able learn innovatively. The purpose of this study was to determine the stages of HOTS-based qirā’ah evaluation with the Quizizz application and its effect on learning outcomes. This study used a true-experimental type of experimental quantitative method (posttest only control group design). The results of this study indicated the value of Std. Experimental error 1.212 and control 1.262, the value of Sig. 0.000 <0.05 means that there was a relationship between the experimental and control post-test variables. The t-count value is 6.341 and the t-table is 2.086, so 6.341 > 2.086 means that Ho was rejected and Ha was accepted. Thus it can be concluded that Quizizz is effectively used in the learning process.